Pengembangan Video Animasi pada Materi Sholat Jama' di Kelas III MIS Rahmah El-Yunusiyyah Padang Panjang (Pusat Riset dan Inovasi Nasional, 2026)
Animated video is one of the media that can be used in the learning process. In grade III of Madrasah Ibtidaiyyah Rahmah El-Yunusiyyah Padang Panjang, students experience difficulties in understanding the concept of jama' prayer, and the learning method used by teachers still relies on textbooks without utilizing varied technology-based media. Consequently, many students' scores remain below the minimum mastery criteria (KKM). Therefore, researchers are interested in developing animated videos as learning media to improve students' scores in the subject of fiqh, specifically on the jama' prayer material. This study aims to: (1) describe the development process of animated videos as learning media for jama' prayer material, (2) determine the validity of the animated video development, and (3) assess the practicality of the animated videos. The research employs the Research and Development (R&D) method with the 4D model (Define, Design, Develop, Disseminate) involving 21 students from grade III of MIS Rahmah El-Yunusiyyah as subjects. Research instruments include expert validation sheets, teacher practicality questionnaires, and student response questionnaires. The research findings indicate that the animated video has very high validity based on material experts (98.2%) and media experts (94%), with practicality reaching 100% under the very practical criteria. Additionally, student responses reached 82.86% in the very interesting category. The developed animated video can be categorized as valid, practical, and effective in enhancing students' understanding of jama' prayer material.